Investigation of differentially expressed genes related to cellular senescence between high-risk and non-high-risk groups in neuroblastoma - Zhou, Xingyu; Wu, Yuying; Qin, Lan; Zeng, Miao; Zhang, Mingying; Zhang, Jun (Frontiers in Cell and Developmental Biology, 2024)
Object: This study aims to identify differentially expressed genes (DEGs) between high-risk and non-high-risk groups in neuroblastoma (NB), construct a prognostic model, and establish a risk score formula. Materials and methods: The NB dataset GSE49710 (n=498) from the GEO database served as the training cohort to select DEGs between high-risk and non-high-risk NB groups. Cellular senescence-related genes were obtained from the Aging Atlas database. Intersection genes from both datasets were identified as key genes of cellular senescence-related genes (SRGs). A prognostic model was constructed using Univariate Cox regression analysis and the Lasso algorithm with SRGs. Validation was performed using the E-MTAB-8248 cohort (n=223). The expression levels of AURKA and CENPA were evaluated via RT-qPCR in two clinical NB sample groups. Results: Eight SRGs were identified, and a prognostic model comprising five genes related to cellular senescence was constructed. AURKA and CENPA showed significant expression in clinical samples and were closely associated with cellular senescence. Conclusion: The prognostic model consisted with five cellular senescence related genes effectively predicts the prognosis of NB patients. AURKA and CENPA represent promising targets in NB for predicting cellular senescence, offering potential insights for NB therapy.